From Products to Immersive Experiences: Synthesising Responsible AI, Marketing, and the Managerial Challenge of Sustainability - Knihová, Ladislava (Publishing House of Wroclaw University of Economics and Business, 2025)
This chapter is a conceptual contribution that builds on recent developments in marketing, particularly the shift from product-centred approaches to immersive, experience-driven strategies. Drawing on the author’s academic insight and practical engagement with AI-enhanced marketing, it offers a managerial perspective on the evolving role of responsible artificial intelligence in designing sustainable customer experiences. In doing so, the chapter presents an Immersive Customer Experience Framework and seeks to advance the discourse on responsible artificial intelligence and immersive experience design by synthesising theoretical insights with emerging industry practices, while also considering the broader managerial implications of sustainability.
Quote as: Knihová, L. (2025). From Products to Immersive Experiences: Synthesising Responsible AI, Marketing, and the Managerial Challenge of Sustainability. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 181-191). Publishing House of Wroclaw University of Economics and Business.
Keywords: concept of the third place; immersive customer experience; immersive marketing; managerial perspective; responsible AI